2019
DOI: 10.1038/s41598-019-53883-y
|View full text |Cite
|
Sign up to set email alerts
|

The coordinated action of RNase III and RNase G controls enolase expression in response to oxygen availability in Escherichia coli

Abstract: Rapid modulation of RNA function by endoribonucleases during physiological responses to environmental changes is known to be an effective bacterial biochemical adaptation. We report a molecular mechanism underlying the regulation of enolase (eno) expression by two endoribonucleases, RNase G and RNase III, the expression levels of which are modulated by oxygen availability in Escherichia coli. Analyses of transcriptional eno-cat fusion constructs strongly suggested the existence of cis-acting elements in the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…In the case of the precursor mRNA of the T7 phage [28,71], RNase III was shown to proceed to single strand cleavages, releasing individual mRNAs with a stable hairpin in their 3 -ends. Other cases of positive regulation by RNase III have been identified, but the mechanism has not been elucidated, such as eno [26], ahpC, pflB, yajQ [32] and sucA [72] mRNAs. The importance of RNase III in the positive regulation of gene expression is further suggested by two independent transcriptomic analyses showing that 23% (120 out of 511 [30]) and 47% (87 out 187 [29]) of the genes whose expression was altered in an rnc mutant were downregulated.…”
Section: Importance Of Rnase III In the Positive Regulation Of Gene E...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the precursor mRNA of the T7 phage [28,71], RNase III was shown to proceed to single strand cleavages, releasing individual mRNAs with a stable hairpin in their 3 -ends. Other cases of positive regulation by RNase III have been identified, but the mechanism has not been elucidated, such as eno [26], ahpC, pflB, yajQ [32] and sucA [72] mRNAs. The importance of RNase III in the positive regulation of gene expression is further suggested by two independent transcriptomic analyses showing that 23% (120 out of 511 [30]) and 47% (87 out 187 [29]) of the genes whose expression was altered in an rnc mutant were downregulated.…”
Section: Importance Of Rnase III In the Positive Regulation Of Gene E...mentioning
confidence: 99%
“…As a consequence, inactivation of RNase III results in the overexpression of PNPase [23]. In a small number of cases, RNase III was also shown to be involved in the positive post-transcriptional regulation of a diverse set of genes, including gadE mRNA, encoding a regulator involved in acid resistance [24]; adhE mRNA encoding an alcohol dehydrogenase essential for fermentation [25]; eno mRNA encoding the metabolic enzyme enolase, which is also associated with the degradosome [26], cIII and N mRNAs from the phage λ [15,27] and the pre-mRNA of phage T7 [28]. Thus, in addition to its role in RNA decay, RNase III is also involved in the positive regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…RNase G is a bacterial endoribonuclease known to negatively regulate gene expression via mRNA decay [9,[15][16][17]; however, SDS-PAGE and mass spectrometry revealed that some SPI-1 T3SS effectors (SlrP, SopA, SipA, and SipC) were up-regulated in the WT strain compared to that in the Δrng strain, indicating that changes in their mRNA levels were not a direct consequence of mRNA decay by RNase G. To assess this further, we analyzed upstream pathways to identify a SPI-1 T3SS repressor that can be negatively regulated by RNase G. When S. Typhimurium invades host cells or responds to elevated sucrose or salt concentrations, SPI-1 T3SS effector gene expression is activated by the major transcriptional activator HilA, which is generally repressed by H-NS [31,35,52]. To explore the relationships between sipA, sipC, hilA, and hns mRNA expression levels, real-time reverse transcription polymerase chain reaction (qRT-PCR) was performed using total RNA from WT cells cultured under aerobic and anaerobic conditions, since SPI-1 T3SS expression is known to be up-regulated during Salmonella growth under low oxygen conditions and during host cell infection [27,53].…”
Section: Effect Of Rnase G Levels On T3ss Activitymentioning
confidence: 99%
“…Both enzymes are single-stranded RNA-specific endoribonucleases with a preference for cleaving AU-rich sequences [11,13,14]. RNase G participates in rRNA maturation and mRNA degradation [9,11,[15][16][17][18][19]. E. coli lacking rne can be made viable by overexpressing RNase G; however, rngcomplementation affects the abundance of a small portion of mRNAs in rne-deficient cells [9], indicating that RNase G and E play distinct physiological roles.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some differences in substrate requirements, both enzymes prefer 5’ end-monophosphorylated RNA and attack single-stranded AU-rich sequences 42 44 . In E. coli , RNase G cleaves the 5’ end of a 16S rRNA precursor 42 and controls the stability of a limited number of mRNAs 45 47 . However, RNase G may have a global role in mRNA stability in some bacteria other than E. coli 48 .…”
Section: Introductionmentioning
confidence: 99%